THE EFFECT OF CUFF RELOCATION FREQUENCY ON NON-INVASIVE BLOOD PRESSURE MONITORING ON THE INCIDENCE OF SKIN IRRITATION IN THE INTENSIVE CARE UNIT - Sugianto; Heru Noor Ramadhan (Universitas Kadiri, 2026)
The bedside monitor is an indispensable tool in the intensive care setting for the continuous assessment of patients’ vital signs. However, the prolonged and intermittent compression inherent in Non-Invasive Blood Pressure (NIBP) monitoring presents a significant risk for Medical Device-Related Pressure Injury (MDRPI), frequently manifesting as skin irritation. This quasi-experimental study, using a time-series design, investigated the optimal frequency of cuff relocation to minimise this risk in the Intensive Care Unit of Dr. Kariadi General Hospital, Semarang. A total of 60 respondents were equally divided into two protocol groups: standard care (cuff relocation every 8 hours) and intervention (cuff relocation every 4 hours). Data were collected via systematic observation and analysed using a simple logistic regression test. The results demonstrated that the 4-hourly relocation protocol significantly reduced the incidence of skin irritation (1.6%) compared to the 8-hourly protocol (3.3%) (p = 0.002). This finding established a statistically significant and clinically relevant influence of increased relocation frequency on reducing the risk of cutaneous injury. The study concludes that mandatory cuff relocation every 4 hours should be adopted as a fundamental practice to enhance patient safety and skin integrity in critical care.